Quality of digital learning media for elementary school teacher education students - Dian Fitri Nur Aini; Maharani Putri Kumalasani; Dian Ika Kusumaningtyas (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2026)
The COVID-19 pandemic, which persisted for two years, significantly impacted various sectors, particularly education and learning environments. However, as COVID-19 cases declined, the government authorized limited face-to-face learning. One essential tool to support both online and offline learning is digital learning media. Such media can be developed by teachers and pre-service teachers based on four aspects: content, instructional design, media and communication, and implementability and user response. This study aimed to provide an in-depth description of the quality of content, instructional design, and constructs of digital learning media developed by elementary school teacher education (PGSD) students. This study employed a qualitative approach with a descriptive design. The research was conducted at the University of Muhammadiyah Malang and the University of Borneo, involving PGSD students from both universities as the research subjects. Data were collected using observation guidelines, questionnaires, assessment instruments, and interviews. The results showed that the average quality score for the content aspect reached 86%, instructional design reached 83%, and the construct aspect reached 85%. All three dimensions demonstrated excellent quality. Ultimately, the utilization of high-quality digital learning media in the teaching and learning process can enhance students' learning motivation.